Peran Ibu Rumah Tangga sebagai Buruh Batu Bata Dalam Meningkatkan Kesejahteraan Keluarga di Gampong Cot Paya Kabupaten Aceh Besar - Muhammad Nazir Basyir; Sabirin Sabirin; Eka Srimulyani (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2023)
Women have a significant role in a family, not only she works in domestic sphere, but also in public, economic productive works. This income generating works inevitably help the family to meet their needs and necessities. However, on the other hands, being in a factory to workers, although a small one like in brick small industry in Cot Paya village Aceh Besar District is not without challenges, as there are some tensions amidst the multiple roles that a woman needs to handle or manage almost at the same time. This paper is aimed to describe the socio-economics life of those women’s workers who are at the same time are also attached the domestic roles within their household. The data from this research was collected from interviews, observations, and document analysis, as a qualitative research. This research found that, from economic point of view, those women are classified as “sejahtera”. The research also confirmed that they still tried to allocate their time for domestic tasks plus social roles within a society. In terms of family, it definitely increased when a wife engaged in earning income through their works in brick small industry through their partly contribution to the household income.